Yayasan UMP receives RM15,000 donation from Alha Alfa Rich Legacy - Nor Salwana, Mohammad Idris (2021)
KUANTAN, 7 November 2021 – Yayasan UMP received a contribution worth RM15,000 from Alha Alfa Rich Legacy (AARL) for student welfare and those in need.